How do Depth of Discharge, C-rate and Calendar Age Affect Capacity Retention, Impedance Growth, the Electrodes, and the Electrolyte in Li-Ion Cells?. Issue 2 (1st February 2022) - Gauthier, Roby; Luscombe, Aidan; Bond, Toby; Bauer, Michael; Johnson, Michel; Harlow, Jessie; Louli, A. J.; Dahn, J. R.
Abstract : Lithium-ion cells testing under different state of charge ranges, C-rates and cycling temperature have different degrees of lithium inventory loss, impedance growth and active mass loss. Here, a large matrix of polycrystalline NMC622/natural graphite Li-ion pouch cells were tested with seven different state of charge ranges (0–25, 0–50, 0–75, 0–100, 75–100, 50–100 and 25%–100%), three different C-rates and at two temperatures. First, capacity fade was compared to a model developed by Deshpande and Bernardi. Second, after 2.5 years of cycling, detailed analysis by dV/dQ analysis, lithium-ion differential thermal analysis, volume expansion by Archimedes' principle, electrode stack growth, ultrasonic transmissivity and X-ray computed tomography were undertaken. These measurements enabled us to develop a complete picture of cell aging for these cells. This then led to an empirical model for cell capacity loss vs SOC range and calendar age. Although these particular cells exhibited substantial positive electrode active mass loss, this did not play a role in capacity retention because the cells were anode-limited during full discharge under all the tests carried out here. However, the positive electrode mass loss was strongly coupled to positive electrode swelling and electrolyte "unwetting" that would eventually cause dramatic failure.